2003
DOI: 10.1097/00008571-200307000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multiple promoters in the human carboxylesterase 2 gene

Abstract: Carboxylesterases are a broad class of enzymes important in the detoxification of many ester- or amide-bond containing xenobiotics. They also activate analgesics, anticancer prodrugs, and other biologically active compounds, such as cocaine and heroin. The objective of this work was to identify the CES2 gene structure, complex 5' untranslated regions and three potential promoters for the initiation of transcription in different human tissues. Using bioinformatics and progressive reverse transcriptase-polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 40 publications
1
29
0
2
Order By: Relevance
“…A novel SNP 1AϾT found in this study changes the translation start codon ATG to TTG. Wu et al (2003) identified three transcription start sites of CES2, resulting in the synthesis of three transcripts with either 78, 629, or 1187 nucleotides in the 5Ј-UTR. Another inframe ATG codon is present 192 nucleotides upstream of the conventional translational initiation codon, and two longer transcripts with 629 and 1187 nucleotides in the 5Ј-UTR can encode an ORF with 64 additional residues at the amino terminus (NP_003860.2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel SNP 1AϾT found in this study changes the translation start codon ATG to TTG. Wu et al (2003) identified three transcription start sites of CES2, resulting in the synthesis of three transcripts with either 78, 629, or 1187 nucleotides in the 5Ј-UTR. Another inframe ATG codon is present 192 nucleotides upstream of the conventional translational initiation codon, and two longer transcripts with 629 and 1187 nucleotides in the 5Ј-UTR can encode an ORF with 64 additional residues at the amino terminus (NP_003860.2).…”
Section: Discussionmentioning
confidence: 99%
“…Construction of Expression Plasmids. The coding region of CES2L (long form) cDNA starts at an additional ATG translation initiation codon located 192 nucleotides upstream of the conventional ATG codon (Wu et al, 2003) and encodes a 623-amino acid protein found in the National Center for Biotechnology Information database (NP_003860.2). The wild-type CES2L cDNA was amplified by PCR from Human Liver QUICK-Clone cDNA (Clontech, Mountain View, CA) using CES2-specific primers, 5Ј-CACCCAC-CTATGACTGCTCA-3Ј and 5Ј-AGGGAGCTACAGCTCTGTGT-3Ј.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although enzymes can be purified from human liver (Humerickhouse et al, 2000), recent studies indicate the presence of genetic variants (Munger et al, 1991;Shibata et al, 1993;Wu et al, 2003) that could influence enzyme expression or catalytic activity. The first successful expression of human carboxylesterase CES1A1 in the Sf9 insect cell system was reported by Kroetz et al (1993).…”
Section: Discussionmentioning
confidence: 99%
“…Large interpatient variability in plasma levels of SN-38 could be indicative of genetic polymorphism. However, pharmacogenomics studies for CES2 have not come to a consensus on the association of SNPs with CES2 expression or activity (Wu et al, 2003;Charasson et al, 2004;Marsh et al, 2004;Kubo et al, 2005).…”
mentioning
confidence: 99%